2018
DOI: 10.1002/ppul.24156
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal enuresis and sleep disordered breathing in primary school children: Potential implications

Abstract: The pathogenic mechanisms linking snoring and unrefreshing sleep to increased risk of NE are unknown. However, snoring, a surrogate reporter of SDB, is associated with increased urine production, while unrefreshing sleep may result from disrupted sleep facilitating increased sleep pressure and elevated arousal thresholds. Thus, both SDB and unrefreshing sleep are potential independent risk factors of NE in school age children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 38 publications
(84 reference statements)
1
20
1
Order By: Relevance
“…Although the clinical relevance of detecting snoring, especially less‐frequent snoring, remains to be established, the present study has shown that snoring 1–6 nights a week is associated with increased airway symptoms, and the systemic symptoms of hypertension, diabetes and heart disease. This finding suggests that less‐frequent snoring might be related to physical and mental disorders, as was observed in the associations between snoring 1–2 nights per week and a higher prevalence of impaired cognitive function or enuresis in children …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although the clinical relevance of detecting snoring, especially less‐frequent snoring, remains to be established, the present study has shown that snoring 1–6 nights a week is associated with increased airway symptoms, and the systemic symptoms of hypertension, diabetes and heart disease. This finding suggests that less‐frequent snoring might be related to physical and mental disorders, as was observed in the associations between snoring 1–2 nights per week and a higher prevalence of impaired cognitive function or enuresis in children …”
Section: Discussionmentioning
confidence: 53%
“…This finding suggests that less-frequent snoring might be related to physical and mental disorders, as was observed in the associations between snoring 1-2 nights per week and a higher prevalence of impaired cognitive function or enuresis in children. 31,32 This study had several limitations. First, Japan Gerontological Evaluation Study 2013 was based on a postal self-reported questionnaire and not on face-to-face interviews or diagnoses by clinical specialists.…”
Section: Discussionmentioning
confidence: 97%
“…Though the relationship between nocturnal enuresis and OSA is well documented in literature, Wada et al examined the less‐understood relationship between the symptoms of SDB, such as snoring, and nocturnal enuresis. This study utilized a standard questionnaire in 20 000 children (age, 5‐12 years) in Japan to examine the associations between nocturnal enuresis and the frequency of unrefreshing sleep and snoring.…”
Section: Introductionmentioning
confidence: 99%
“…In pediatrics, the first‐line treatment for uncomplicated OSA is AT . Several guidelines recommend obtaining a PSG before obtaining an AT . The American Academy of Otolaryngology—Head and Neck Surgery (AAO‐HNS), recommends obtaining a PSG in those patients considered high risk for surgical morbidity or those where there is disconnect between patient symptoms and the physical examination .…”
Section: Introductionmentioning
confidence: 99%
“…Primary snoring during sleep is currently thought to exist at the mild, non-pathological, end of a continuum of airway obstruction with medically-recognized obstructive sleep apnea (OSA) at the extreme end. Primary snoring has long been statistically linked to significantly increased risk of hypertension [6], heart disease and stroke [7], premature births [8], and in children, to developmental delay, attention deficit disorder, and socialization and learning disabilities [9]. Recently reported research has also identified two blood pressure-related phenomena linked to snoring; (1) lack of normal blood pressure 'dipping,' [11] and (2) the occurrence of a blood pressure surge following snoring episodes [12].…”
Section: Introductionmentioning
confidence: 99%